Remanufacturing Process And Its Challenges - Andrew Munot, Magdalene; Ibrahim, R.N. (Universiti Malaysia Pahang, 2013)
In the recent years, remanufacture of used-products is becoming an important production activity amongst many companies. This is primarily motivated by the strict environmental regulations, increasing customers’ awareness of green environment and economical benefits. Remanufacturing is an industrial process that involves four key processes, namely inspection/grading, disassembly, component reprocessing and reassembly/testing. It is established that the presence and interactions of several unique characteristics within the remanufacturing systems implicates subsequent key processes. These unique characteristics would become challenges to production planning and control activity in any remanufacturing systems. Consequently, it is very imperative that these characteristics are properly taken into account in any production planning and control activity.